2005
DOI: 10.1128/aac.49.9.3624-3630.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Polymyxin B against Pseudomonas aeruginosa

Abstract: Despite limited data, polymyxin B (PB) is increasingly used clinically as the last therapeutic option for multidrug-resistant (MDR) gram-negative bacterial infections. We examined the in vitro pharmacodynamics of PB against four strains of Pseudomonas aeruginosa. Clonal relatedness of the strains was assessed by random amplification of polymorphic DNA. Time-kill studies over 24 h were performed with approximately 10 5 and 10 7 CFU/ml of bacteria, using PB at 0, 0.25, 0.5, 1, 2, 4, 8, and 16؋ MIC. Dose fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 22 publications
10
140
1
5
Order By: Relevance
“…Polymyxins are known to displace the calcium and magnesium bridges that stabilize the LPS (Evans et al, 1999;Hancock, 1997b;Hermsen et al, 2003;Tam et al, 2005). Both pmrHFIJKLM and PQS are induced in the exponential growth phase when P. aeruginosa is grown in magnesium-limiting media (Guina et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Polymyxins are known to displace the calcium and magnesium bridges that stabilize the LPS (Evans et al, 1999;Hancock, 1997b;Hermsen et al, 2003;Tam et al, 2005). Both pmrHFIJKLM and PQS are induced in the exponential growth phase when P. aeruginosa is grown in magnesium-limiting media (Guina et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Polymyxin showed rapid bactericidal activity in vitro and the PD of polymyxin B is most closely linked to the AUC/MIC ratio. 18 Based on our and previous time -kill studies, monotherapy with polymyxin B leads to rapid initial decline followed by extensive regrowth. Hence, the combination regimens with administration of polymyxin in a high-intensity fashion, based on the mechanism-based modelling, provided an effective way of addressing the subpopulations that are resistant to either polymyxin B or doripenem.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Previous in vitro studies have shown that polymyxin combinations with a carbapenem are highly bactericidal against A. baumannii 17 although the rapid bactericidal activity of this combination is followed by regrowth with the emergence of resistant subpopulations. 18 Therefore, this underscores the need to develop novel strategies to combat A. baumannii focused on polymyxin combinations to maximize bactericidal activity, minimize resistance and decrease drug exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed in recent years using a pharmacodynamic model or standard time-kill studies of the effect of polymyxin B or colistin against strains of P. aeruginosa (19,59,67,93,107,166), A. baumannii (60,88,106,136,160,170), and K. pneumoniae (20). Nearly all studies demonstrated that the polymyxins produce concentration-dependent killing, with an initial kill followed by regrowth.…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 99%